Archipelascape a Master Plan for Regenerating the Archipelagic Country - Prayitno, Budi (2006)
The regeneration of coastal cities is one of the key architecrurai, urban design and planning introvct/on wirh the of i?:bJii.sirial declitre. enhance liveabiliry and susfainabiiity atis' transform (he inrage of fire ineiorresi~n archipelagic atid marine decline. Thtrs. the variot~s dssign and plnnnitrg ttrodel for wcterfont regeneration could be able to develo? and crparrd ittro rrri.red-use atrd itvbrid function which invenr new'conjunction of public arrdprivate inreresf. in this emerging water-ont projecs, inter-cocrstai cities conperilion turns the ciy info a procirrct wirich is marketed and sold, foarsing auentiotr on the imagety which iconed fire cify and drreren~iares it fieom ofher coartni cifics. Such images includes icon~gruphy of local waterfront avd function is linked ro rlic rise brand niarkring irr fhc at.chipelagic conte.rr. These planalng acfivities show there have lcetr a wid2 a r r q of res,"onses rhe opporftrnities and problctns associaicd r:..?ir spn:inl rrenror/rs of constal orens of nrc~ropolirim citiex They rccogtriie a process stnrrirrg 111irh grotrbrg fire tiodcs (coastal activities cenfers) and clrateritrg soltre sirb spatid trmc-or-h rirrorrgir biidging them by warer transp'ortation sysretns. This proce.+ is siroped by crenfi/;g tntri[i-lcyercd nehvork of regional coastal ciries into sonre clrisrers and corridors it1 the conte-rt of waferfiont metropoliron regeneration in archipelagic country. There are flrree Izvel of neovotk in archipelagic spatiill p1ati:;ing concepts thar is cirics ncnvoik, region01 nefivor.k (intra-island and itirer-islmrtl) and global nehoork for fosreritrg tire abiliy of oiher rcgiotis fo rivol .Icrkcrrtcr city ~lott~itrcrtrcitcr octivitic.r cmrd clrar~~itpigot vcr. Ti1i.r is only whan rhe regiotral coasral ciries have acqtrired (his power can (here be a harmonifation of centralized and deccn frolized plontring policy.